『蜻蛉日記』における夢 [Dreams in The Gossamer Years] - Sonoyama, Senri (Silva Iaponicarum, 2024)
Science has yet to resolve many mysteries about dreams, such as why people dream and how dreams are created. Therefore, dreams are categorized as beyond imagination, different from reality. When dreams are expressed in the form of literature, they take on a more fantastic atmosphere. In this article, I focus on dreams in ancient times and consider what it means to use dreams as the subject matter of literature. There have already been many prominent studies on dreams in ancient times, including Saigō Nobutsuna’s Ancient People and Dreams (Heibonsha, 1993). Utilizing these studies, I focus on the Kagerō Nikki (The Gossamer Years). I conclude that the four waka poems about ‘dreams’ in The Gossamer Years were an exchange with Tōshi, a person she could truly trust, and that for Michitsuna-no haha they symbolised a peaceful life in the real world.